Design of Refractive/Diffractive Hybrid Projection Lens for DMD-Based Maskless Lithography - Zhuohui Xu; Jinyun Zhou; Bo Wang; Ziming Meng (Optics, 2021)
The projection lens is the core component of DMD-based maskless lithography and its imaging quality directly affects the transferal of exposure pattern. Based on the traditional projection lens system, we have designed diffractive optical element (DOE) and aspheric surfaces to optimize the refractive/diffractive hybrid projection lens system to improve its imaging quality. We found that the best effect is obtained when DOE is very close to the front lens group before the diaphragm of the hybrid system. Compared with the traditional projection lens system, this hybrid projection lens system has lower wave aberration with the help of DOE, and higher image quality owing to the modulation transfer function (MTF) value being improved. Finally, a hybrid projection lens system with working distance of 29.07 mm, image Space NA of 0.45, and total length of 196.97 mm is designed. We found that the maximum distortion and field curvature are 1.36 × 10−5% and 0.91 μm, respectively.